Avaliação do uso de antibioticoprofilaxia em cirurgias realizadas em hospital do sul de Santa Catarina - Silva, Alexandre da (2016)
Introduction: The evolution of antibiotics changed the prognosis of surgical site infections (SSI), however its indiscriminate use throughout the years lead to antimicrobial resistance. The rational use of antibiotics makes the treatment of infections more efficient, increases patient’s quality of life and helps the hospital save money. Goal: The study analyzed the use of antibiotic prophylaxis in elective surgeries performed in a large hospital located in southern Santa Catarina. Methods: A prospective cross-sectional study to analyze the administration of antibiotic prophylaxis. When there was normal distribution of the results, Pearson’s chi-squared test and Student’s t-test were used. When there was abnormal distribution, Spearman’s correlation test or Mann-Whitney U test was used. Results: The study analyzed 1,156 surgeries performed between June and November of 2014. 54% of the surgeries were orthopedic, 32% gastrointestinal, 7,8% plastic surgeries and 6,2% cardiac. Among all the surgeries, 68,5% had no indication of prophylaxis, 78,4% were considered clean with no indication of prophylaxis, 41% of the patients didn’t receive the proper dose of antibiotic according to their weight, 75% of the surgeries the antibiotic was administrated outside the 30-minute pre incision and in 47% of the surgeries prophylaxis went beyond 24 hours. Antibiotics were administrated and SSI still appeared in 24 (68,6%) out of 35 surgeries. Conclusion: It was concluded that there were inadequacies in the administration of antibiotics in all stages of the process. The non-conformities in the administration suggest a low adherence to compliance with existing protocols and the protocols of the institution must be accompanied by CCIH and clinical hospital pharmacy.